Flame structure and laminar burning speed of gas to liquid fuel air mixtures at moderate pressures and high temperatures. (1st December 2017) - Wang, Ziyu; Alswat, Mohammed; Yu, Guangying; Allehaibi, Moaz Omar; Metghalchi, Hameed
Abstract: Gas to liquid (GTL) fuel, synthesized from natural gas through Fisher–Tropsch (F–T) process, has gained significant attention due to its cleaner combustion characteristics when compared to conventional fuels. Combustion properties such as flame structure and laminar burning speed of GTL/air mixture premixed flames have been investigated. The GTL fuel used in this research was provided by Air Force Research Laboratory (AFRL), designated by Syntroleum S-8, which was derived from natural gas via F–T process. A mixture of 32% iso-octane, 25% n-decane, and 43% n-dodecane by volume is considered as the surrogates of GTL fuel for filling process. Experiments were conducted using a cylindrical chamber to study the flame structure and a spherical chamber for laminar burning speeds measurement. The cylindrical chamber was set up in a Z-shape schlieren system coupled with a high-speed CMOS camera that was used to capture evolutionary behavior of flames at up to 40, 000 frames per second. Pressure rise as a function of time during the flame propagation in the spherical vessel was the primary input of the multi-shell thermodynamic model used to calculate the laminar burning speed for the smooth flames. Power law correlations over a wide range of pressures (from 0.5 atm up to 4.3 atm), temperatures (from 490 K up to 620 K), and equivalence ratios (from 0.7 to 1.2) have been developed for laminar burning speeds of GTL/air flames. Experimental burning speed results have been compared with simulation values obtained by the solution of one dimensional steady premixed flame code from CANTERA using Ranzi's chemical kinetics mechanisms. Comparisons show very good agreement with the available experimental data in this study.